A magnesium alloy composite coating and preparation method thereof

By constructing a microarc oxide layer and gel layer on the surface of magnesium alloy, the problems of magnesium alloy not resistant to corrosion and lack of antibacterial ability are solved, and the comprehensive performance of thermal control, anticorrosion and antibacterial are achieved, which is suitable for the heat dissipation and antibacterial needs of electronic products. .

CN118422295BActive Publication Date: 2025-02-18CHONGQING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410505513.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-25
Publication Date
2025-02-18
Estimated Expiration
2044-04-25

AI Technical Summary

Technical Problem

Magnesium alloy itself is not corrosion-resistant, has a low hemispherical emissivity, and lacks antibacterial ability, which cannot meet the requirements of electronic products for heat dissipation and antibacteriality.

Method used

The composite coating process of microarc oxide layer and gel layer is adopted. The microarc oxide layer contains Ag and Zn elements, and the gel layer contains Ti elements. By constructing micron-scale metal oxides, the corrosion resistance and antibacteriality of magnesium alloys are improved. ability.

Benefits of technology

The thermal control, anti-corrosion and antibacterial functions of magnesium alloy substrate are realized, the hemispherical emissivity and corrosion resistance are improved, and the spatial environment stability is good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118422295B_ABST
    Figure CN118422295B_ABST
Patent Text Reader

Abstract

The present invention discloses a magnesium alloy composite coating and a preparation method thereof. The magnesium alloy composite coating comprises: a micro-arc oxidation layer and a gel layer. The micro-arc oxidation layer comprises Ag and Zn elements, and the gel layer comprises Ti element; wherein the content of Ag element in the micro-arc oxidation layer is not less than 0.05%, the content of Zn element is not less than 0.6%; and the content of Ti element in the gel layer is not less than 8%. The present invention utilizes the micro-arc oxidation layer and the gel layer to construct micron-level metal oxides to improve the hemispherical emissivity and the corrosion resistance of the magnesium alloy substrate. At the same time, appropriate amounts of Ag, Zn, Ti and other elements are added to the micro-arc oxidation layer and the gel layer, which also improves the antibacterial ability of the magnesium alloy substrate. The formed composite coating has the comprehensive performance of thermal control, corrosion resistance and antibacterial, and has good space environment stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings and relates to a magnesium alloy composite coating and a preparation method thereof. Background Art

[0002] The interior of a manned sealed cabin has conditions suitable for the survival of microorganisms. If antibacterial measures are not taken, bacteria and fungi will grow in large numbers, affecting the safety of personnel and equipment facilities in the sealed cabin. In order to eliminate the impact of internal heat and microorganisms, the surfaces of electronic loads such as microwave devices and semiconductor devices in the manned sealed cabin should be prepared with a covering layer with thermal control, anti-corrosion and antibacterial functions.

[0003] With the development of spacecraft models, on the one hand, the demand for spacecraft payloads to reduce weight has become increasingly obvious due to the gradual enlargement of spacecraft payloads. On the other hand, higher requirements are placed on the corrosion resistance and thermal control capabilities of electronic payloads such as microwave devices, T / R components, and semiconductor device surfaces.

[0004] For example, patent CN115975476A provides a low-vacuum volatile antibacterial decorative coating, a preparation method and its application. The raw materials of the coating include the following components in mass fraction: 1-1.5 parts of quaternary ammonium salt-modified epoxy resin, 0.5-1 parts of polyamide resin, 5-6 parts of butyl acetate, 0.5-1 parts of n-butanol, 0.1-0.2 parts of multiple composite TiO2 nano-antibacterial particles, 1-1.5 parts of titanium dioxide, and 0.01-1.5 parts of inorganic colored pigments. Among them, the multiple composite TiO2 nano-antibacterial particles are graphene-coated doped nano-titanium dioxide, and the multiple composite TiO2 nano-antibacterial particles are prepared by adding them to the coating, and the composition and proportion of the coating are optimized to solve the problems of low antibacterial efficiency and poor dispersibility of photocatalyst TiO2. The coating has excellent antibacterial and environmental performance and can meet the needs of antibacterial decoration in manned cabins.

[0005] Magnesium alloys are favored in the aerospace field because of their low density, but magnesium alloys themselves are not corrosion-resistant, and the hemispherical emissivity of the metal surface itself is low and does not have antibacterial ability, which cannot meet the requirements of heat dissipation and antibacterial for electronic products. Therefore, surface thermal control anticorrosion and antibacterial treatment is required to meet the use requirements of electronic load parts.

[0006] Therefore, exploring the coating attached to the surface of magnesium alloy to prepare a material with low absorption ratio, high anti-mildew performance and strong corrosion resistance is an urgent problem to be solved by technical personnel in this field. Summary of the invention

[0007] In view of the defects existing in the above-mentioned prior art, the present invention provides a magnesium alloy composite coating and a preparation method thereof, wherein the magnesium alloy composite coating comprises: a micro-arc oxidation layer and a gel layer, wherein the micro-arc oxidation layer comprises Ag and Zn elements, and the gel layer comprises Ti elements; wherein the content of Ag element in the micro-arc oxidation layer is not less than 0.05%, the content of Zn element is not less than 0.6%; and the content of Ti element in the gel layer is not less than 8%. The present invention utilizes the micro-arc oxidation layer and the gel layer to construct micron-level metal oxides to improve the hemispherical emissivity and the corrosion resistance of the magnesium alloy substrate. Meanwhile, the addition of appropriate amounts of Ag, Zn, Ti and other elements to the micro-arc oxidation layer and the gel layer also improves the antibacterial ability of the magnesium alloy substrate. The formed composite coating has the comprehensive properties of thermal control, corrosion resistance and antibacterial, and has good space environment stability.

[0008] In a first aspect, the present invention provides a magnesium alloy composite coating, comprising: a micro-arc oxidation layer and a gel layer, wherein the micro-arc oxidation layer comprises Ag and Zn elements, and the gel layer comprises Ti elements;

[0009] The content of Ag element in the micro-arc oxidation layer is not less than 0.05%, the content of Zn element is not less than 0.6%; and the content of Ti element in the gel layer is not less than 8%.

[0010] Furthermore, the phases of the micro-arc oxidation layer include Ag2O, ZnO, and MgO, and the phases of the gel layer include TiO2, (TiO) n ,TiO(OH)2.

[0011] Furthermore, the thickness of the magnesium alloy composite coating is 100-140 μm, the thickness of the micro-arc oxidation layer is 30-50 μm, and the thickness of the gel layer is 70-90 μm.

[0012] Furthermore, the hemispherical emissivity is ≥0.85, the solar absorption ratio is ≤0.4, the absorption-emission ratio is ≤0.5, the mildew resistance level is ≤1, the antibacterial rate is ≥90%, and the neutral salt spray resistance is ≥192h.

[0013] In a second aspect, the present invention further provides a method for preparing the above-mentioned magnesium alloy composite coating, which specifically comprises the following steps:

[0014] S1: Wipe with organic solvent to clean the oil stain on the surface of magnesium alloy;

[0015] S2: The magnesium alloy of S1 is roughened to make the roughness ≥3.2;

[0016] S3: performing micro-arc oxidation treatment on the magnesium alloy of S2, and drying it to obtain a micro-arc oxidation layer containing Ag and Zn elements;

[0017] S4: spraying solvent gel on the surface of the magnesium alloy having the micro-arc oxidation layer containing Ag and Zn elements obtained in S3, drying, and attaching a gel layer containing Ti elements on the surface of the micro-arc oxidation layer to obtain a magnesium alloy composite coating.

[0018] Furthermore, in step S2, the roughening treatment includes at least one of sandblasting, grinding, alkali washing, acid washing, and activation.

[0019] Further, step S3 specifically includes the following steps:

[0020] S31: preparing an electrolyte, the electrolyte comprising: 8-15 g / L sodium silicate, 10-15 g / L sodium pyrophosphate, 8-15 g / L sodium succinate, 10-15 g / L potassium hydroxide, 10-15 mL / L ammonia water, 2-3 g / L zinc oxide, and 0.1-0.2 g / L silver nitrate;

[0021] S32: using the magnesium alloy obtained in S2 as an anode, placing it in an electrolytic cell with an electrolyte, applying a DC voltage to the anode and the cathode to generate a micro-arc discharge, wherein the temperature of the electrolyte is 15-35° C., the forward voltage is 460-500 V, the forward duty cycle is 10-20%, the forward frequency is 800-1000 Hz, and the negative voltage is 60-80 V, the negative duty cycle is 5%-10%, and the negative frequency is 500-600 Hz;

[0022] S33: After the micro-arc oxidation is continued for 30 to 40 minutes, the micro-arc oxidation layer is rinsed with deionized water and dried to obtain a micro-arc oxidation layer containing Ag and Zn elements.

[0023] Furthermore, in step S33, the drying temperature is 60-80°C, and the drying time is 1-2 hours.

[0024] Further, step S4 specifically includes the following steps:

[0025] S41: preparing a first solution and a second solution respectively, wherein the first solution comprises ethanol and butyl titanate, the mass ratio of ethanol to butyl titanate is 5:(2-4), and the second solution comprises ethanol and diethanolamine, the mass ratio of ethanol to diethanolamine is 5:(0.08-0.13);

[0026] S42: the first solution and the second solution are mixed to form a mixed solution, and the mixed solution is magnetically stirred for 1 to 3 hours at a stirring temperature of 50 to 60° C. to obtain a sol-gel;

[0027] S43: spraying the sol-gel onto the surface of the micro-arc oxidation layer containing Ag and Zn elements obtained in S3 with a spray gun, wherein the distance between the spray gun and the surface of the micro-arc oxidation layer is 40 to 70 cm, and the number of spraying is 3 to 5 times;

[0028] S44: After spraying, drying is performed to obtain a gel layer containing Ti element attached to the micro-arc oxidation layer.

[0029] Furthermore, in step S44, the drying is performed by first drying in the shade and then drying by heating, the drying time in the shade is 3 to 5 hours, the drying temperature is 60 to 80° C., and the drying time is 20 to 30 hours.

[0030] The present invention provides a magnesium alloy composite coating and a preparation method thereof, which at least comprises the following steps:

[0031] Beneficial effects:

[0032] (1) The present invention adopts the preparation process of micro-arc oxidation and sol-gel to obtain a composite coating attached to a magnesium alloy. The micro-arc oxidation film layer and the gel layer improve the corrosion resistance of the magnesium alloy substrate. The appropriate amount of Ag and Zn elements added to the micro-arc oxidation layer and the appropriate amount of Ti element added to the gel layer also improve the antibacterial ability of the magnesium alloy substrate, and simultaneously realize the functions of thermal control, corrosion protection and antibacterial on the surface of materials such as magnesium alloys for electronic products and semiconductor devices.

[0033] (2) The present invention constructs a micron-level metal oxide by using a micro-arc oxidation layer and a gel film layer in the magnesium alloy composite coating to achieve a hemispherical emissivity higher than 0.85, which can meet the heat dissipation requirements of electronic products such as cabin chassis and frames.

[0034] (3) In the micro-arc oxidation process of the present invention, sodium silicate and sodium pyrophosphate are used as the main salts of micro-arc oxidation, and are mainly used to be adsorbed on the surface of parts as the main film-forming substances during the micro-arc oxidation process.

[0035] Sodium succinate, potassium hydroxide and ammonia water are used as auxiliary film-forming agents, which mainly play the role of adjusting pH value, stabilizing the micro-arc oxidation solution system and assisting film formation. Zinc oxide and silver nitrate are used as antibacterial additives, which have the effect of inhibiting bacterial growth.

[0036] (4) In the sol-gel process of the present invention, butyl titanate is used as the main salt of the sol-gel and is mainly used as the main film-forming substance to form the film layer skeleton in the sol-gel process.

[0037] Ethanol and diethanolamine, as solvents and auxiliary film-forming agents, mainly play the role of regulating the hydrolysis and cross-linking speed of butyl titanate.

[0038] (5) The magnesium alloy composite coating preparation process provided by the present invention has the advantages of simple process route and convenient operation. The formed thermal control anti-corrosion and antibacterial coating has a wide spectrum of antibacterial effects and good spatial environmental stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is an appearance diagram of the magnesium alloy composite coating of Example 1 provided by the present invention;

[0040] Figure 2 This is a microscopic morphology of the magnesium alloy composite coating of Example 1 provided by the present invention;

[0041] Figure 3 This is an appearance diagram of the magnesium alloy composite coating of Example 1 provided by the present invention after being subjected to a 210h neutral salt spray test;

[0042] Figure 4 This is an appearance diagram of the magnesium alloy composite coating of Example 1 provided by the present invention after being subjected to anti-mildew and antibacterial tests. DETAILED DESCRIPTION

[0043] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.

[0045] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.

[0046] In order to eliminate the influence of internal heat and microorganisms, the surface of electronic payload parts such as microwave devices in manned sealed cabins should be prepared with a covering layer with thermal control, anti-corrosion and antibacterial functions.

[0047] In a first aspect, the present invention provides a magnesium alloy composite coating, comprising: a micro-arc oxidation layer and a gel layer, wherein the micro-arc oxidation layer comprises Ag and Zn elements, and the gel layer comprises Ti elements;

[0048] The content of Ag element in the micro-arc oxidation layer is not less than 0.05%, the content of Zn element is not less than 0.6%; and the content of Ti element in the gel layer is not less than 8%.

[0049] Furthermore, the phases of the micro-arc oxidation layer include Ag2O, ZnO, and MgO, and the phases of the gel layer include TiO2, (TiO) n ,TiO(OH)2.

[0050] Furthermore, the thickness of the magnesium alloy composite coating is 100-140 μm, the thickness of the micro-arc oxidation layer is 30-50 μm, and the thickness of the gel layer is 70-90 μm.

[0051] Furthermore, the hemispherical emissivity is ≥0.85, the solar absorption ratio is ≤0.4, the absorption-emission ratio is ≤0.5, the mildew resistance level is ≤1, the antibacterial rate is ≥90%, and the neutral salt spray resistance is ≥192h.

[0052] In a second aspect, the present invention further provides a method for preparing the above-mentioned magnesium alloy composite coating, which specifically comprises the following steps:

[0053] S1: Wipe with organic solvent to clean the oil stain on the surface of magnesium alloy;

[0054] S2: The magnesium alloy of S1 is roughened to make the roughness ≥3.2;

[0055] S3: performing micro-arc oxidation treatment on the magnesium alloy of S2, and drying it to obtain a micro-arc oxidation layer containing Ag and Zn elements;

[0056] S4: spraying solvent gel on the surface of the micro-arc oxidation layer containing Ag and Zn elements obtained in S3, drying, and attaching a gel layer containing Ti elements on the surface of the micro-arc oxidation layer to obtain a magnesium alloy composite coating.

[0057] Furthermore, in step S2, the roughening treatment includes at least one of sandblasting, grinding, alkali washing, acid washing, and activation.

[0058] Further, step S3 specifically includes the following steps:

[0059] S31: preparing an electrolyte, the electrolyte comprising: 8-15 g / L sodium silicate, 10-15 g / L sodium pyrophosphate, 8-15 g / L sodium succinate, 10-15 g / L potassium hydroxide, 10-15 mL / L ammonia water, 2-3 g / L zinc oxide, and 0.1-0.2 g / L silver nitrate;

[0060] S32: using the magnesium alloy obtained in S2 as an anode, placing it in an electrolytic cell with an electrolyte, applying a DC voltage to the anode and the cathode to generate a micro-arc discharge, wherein the temperature of the electrolyte is 15-35° C., the forward voltage is 460-500 V, the forward duty cycle is 10-20%, the forward frequency is 800-1000 Hz, and the negative voltage is 60-80 V, the negative duty cycle is 5%-10%, and the negative frequency is 500-600 Hz;

[0061] S33: After the micro-arc oxidation is continued for 30 to 40 minutes, the micro-arc oxidation layer is rinsed with deionized water and dried to obtain a micro-arc oxidation layer containing Ag and Zn elements.

[0062] Furthermore, in step S33, the drying temperature is 60-80°C, and the drying time is 1-2 hours.

[0063] Further, step S4 specifically includes the following steps:

[0064] S41: preparing a first solution and a second solution respectively, wherein the first solution comprises ethanol and butyl titanate, the mass ratio of ethanol to butyl titanate is 5:(2-4), and the second solution comprises ethanol and diethanolamine, the mass ratio of ethanol to diethanolamine is 5:(0.08-0.13);

[0065] S42: the first solution and the second solution are mixed to form a mixed solution, and the mixed solution is magnetically stirred for 1 to 3 hours at a stirring temperature of 50 to 60° C. to obtain a sol-gel;

[0066] S43: spraying the sol-gel onto the surface of the micro-arc oxidation layer containing Ag and Zn elements obtained in S3 with a spray gun, wherein the distance between the spray gun and the surface of the micro-arc oxidation layer is 40 to 70 cm, and the number of spraying is 3 to 5 times;

[0067] S44: After spraying, drying is performed to obtain a gel layer containing Ti element attached to the micro-arc oxidation layer.

[0068] Furthermore, in step S44, the drying is performed by first drying in the shade and then drying by heating, the drying time in the shade is 3 to 5 hours, the drying temperature is 60 to 80° C., and the drying time is 20 to 30 hours.

[0069] Embodiment 1:

[0070] The magnesium alloy composite coating provided in this embodiment uses MB15 magnesium alloy parts as magnesium alloy, and prepares the composite coating on the MB15 magnesium alloy parts, including a micro-arc oxidation layer and a gel layer, wherein the content of Ag element in the micro-arc oxidation layer is 0.063%, the content of Zn element is 0.83%, and the content of Ti element in the gel layer is 8.5%.

[0071] The phases of the micro-arc oxidation layer include Ag2O, ZnO, MgO, etc., and the phases of the gel layer include TiO2, (TiO) n , TiO(OH)2, etc.

[0072] The preparation scheme of the magnesium alloy composite coating specifically includes the following steps:

[0073] S1: Wipe with organic solvent to clean the oil stains on the surface of magnesium alloy. Use ethanol and acetone to wipe MB15 magnesium alloy parts successively to clean the surface oil stains.

[0074] S2: performing a roughening treatment on the MB15 magnesium alloy parts after cleaning, wherein the roughening treatment method is: performing a subtractive cleaning, a pickling and an activation treatment on the MB15 magnesium alloy parts in sequence, so that the surface roughness of the MB15 magnesium alloy parts is 3.2.

[0075] S3: The MB15 magnesium alloy parts after roughening are subjected to micro-arc oxidation treatment and dried to obtain a micro-arc oxidation layer containing Ag and Zn elements.

[0076] The process of micro-arc oxidation treatment is as follows:

[0077] First, prepare an electrolyte, which includes: 8 g / L sodium silicate, 10 g / L sodium pyrophosphate, 8 g / L sodium succinate, 10 g / L potassium hydroxide, 15 mL / L ammonia water, 3 g / L zinc oxide, and 0.1 g / L silver nitrate;

[0078] Then, the MB15 magnesium alloy part is used as the anode, and the stainless steel plate is used as the cathode. The anode and the cathode are placed in an electrolytic cell with an electrolyte, and the experimental conditions and parameters of micro-arc oxidation are set, such as: the temperature of the electrolyte is 35°C, a DC voltage is applied to the anode and the cathode to generate micro-arc discharge, the forward voltage is 460V, the forward duty cycle is 20%, and the forward frequency is 1000Hz, and the negative voltage is 60V, the negative duty cycle is 5%, and the negative frequency is 500Hz;

[0079] Finally, after continuous micro-arc oxidation for 30 minutes, the micro-arc oxidation layer containing Ag and Zn elements was obtained by rinsing with deionized water and drying at 70°C for 1.5 hours.

[0080] S4: spraying sol-gel on the surface of the micro-arc oxidation layer containing Ag and Zn elements, drying, and attaching a gel layer containing Ti elements on the surface of the micro-arc oxidation layer containing Ag and Zn elements to obtain a magnesium alloy composite coating.

[0081] The sol-gel process is as follows:

[0082] First, a first solution and a second solution are prepared respectively, wherein the first solution includes ethanol and butyl titanate, the mass ratio of ethanol to butyl titanate is 5:3, and the second solution includes ethanol and diethanolamine, the mass ratio of ethanol to diethanolamine is 5:0.1.

[0083] Then, the first solution and the second solution were mixed to form a mixed solution, and the mixed solution was magnetically stirred for 3 hours at a stirring temperature of 50° C. to obtain a sol-gel;

[0084] Afterwards, the spray gun sprays the sol-gel onto the surface of the micro-arc oxidation layer containing Ag and Zn elements obtained in S3. During the spraying, the distance between the spray gun and the surface of the micro-arc oxidation layer containing Ag and Zn elements is 60 cm, and the number of spraying is 4 times.

[0085] Finally, after spraying, drying is performed to obtain a gel layer containing Ti elements attached to the micro-arc oxidation layer containing Ag and Zn elements. The drying is performed by first drying in the shade and then drying by heating, the drying time in the shade is 3 hours, the drying temperature is 60° C., and the drying time is 24 hours.

[0086] The appearance of magnesium alloy composite coating is as follows Figure 1 As shown, the prepared magnesium alloy composite coating was subjected to microscopic analysis ( Figure 2 ), the thickness of the magnesium alloy composite coating is about 127μm, the thickness of the micro-arc oxidation layer is about 38μm, and the thickness of the gel layer is about 89μm.

[0087] Embodiment 2:

[0088] Based on Example 1, Example 2 adjusts the following parameters.

[0089] The magnesium alloy composite coating provided in this embodiment includes a micro-arc oxidation layer and a gel layer, wherein the content of Ag element in the micro-arc oxidation layer is 0.065%, the content of Zn element is 0.72%, and the content of Ti element in the gel layer is 8.8%.

[0090] The process of micro-arc oxidation treatment is as follows:

[0091] Prepare an electrolyte, the electrolyte comprising: 15 g / L sodium silicate, 12 g / L sodium pyrophosphate, 15 g / L sodium succinate, 10 g / L potassium hydroxide, 10 mL / L ammonia water, 2 g / L zinc oxide, and 0.1 g / L silver nitrate;

[0092] The experimental conditions and parameters of micro-arc oxidation were set, such as: the temperature of the electrolyte was 20°C, a DC voltage was applied to the anode and cathode to generate micro-arc discharge, the forward voltage was 470V, the forward duty cycle was 10%, the forward frequency was 1000Hz, the negative voltage was 80V, the negative duty cycle was 10%, and the negative frequency was 600Hz.

[0093] After continuous micro-arc oxidation for 40 minutes, the micro-arc oxidation layer containing Ag and Zn elements was obtained by rinsing with deionized water and drying at 60°C for 2 hours.

[0094] The sol-gel process is as follows:

[0095] The first solution and the second solution are mixed to form a mixed solution, and the mixed solution is magnetically stirred for 2 hours at a stirring temperature of 60° C. to obtain a sol-gel;

[0096] During spraying, the distance between the spray gun and the surface of the micro-arc oxidation layer containing Ag and Zn elements was 60 cm, and the number of spraying times was 3 times.

[0097] After spraying, drying is performed to obtain a gel layer containing Ti elements attached to the micro-arc oxidation layer containing Ag and Zn elements. The drying is performed by first drying in the shade and then drying by heating. The shade drying time is 5 hours, the drying temperature is 70° C., and the drying time is 20 hours.

[0098] Microscopic analysis of the prepared magnesium alloy composite coating showed that the thickness of the magnesium alloy composite coating was about 120 μm, the thickness of the micro-arc oxidation layer was about 46 μm, and the thickness of the gel layer was about 74 μm.

[0099] Embodiment 3:

[0100] Based on Example 1, Example 3 adjusts the following parameters.

[0101] The magnesium alloy composite coating provided in this embodiment uses MB15 magnesium alloy parts as magnesium alloy, and prepares the composite coating on the MB15 magnesium alloy parts, including a micro-arc oxidation layer and a gel layer, wherein the content of Ag element in the micro-arc oxidation layer is 0.062%, the content of Zn element is 0.74%, and the content of Ti element in the gel layer is 8.5%.

[0102] The process of micro-arc oxidation treatment is as follows:

[0103] Prepare an electrolyte, the electrolyte comprising: 3 g / L zinc oxide and 0.2 g / L silver nitrate;

[0104] MB15 magnesium alloy parts are used as anodes, and stainless steel is used as cathodes. The anodes and cathodes are placed in an electrolytic cell with electrolyte, and the experimental conditions and parameters of micro-arc oxidation are set, such as: the temperature of the electrolyte is 15°C, a DC voltage is applied to the anode and cathode to generate micro-arc discharge, the forward voltage is 500V, the forward duty cycle is 20%, and the forward frequency is 800Hz.

[0105] Microscopic analysis of the prepared magnesium alloy composite coating showed that the thickness of the magnesium alloy composite coating was about 123 μm, the thickness of the micro-arc oxidation layer was about 38 μm, and the thickness of the gel layer was about 85 μm.

[0106] Embodiment 4:

[0107] Based on Example 1, Example 4 adjusts the following parameters.

[0108] The magnesium alloy composite coating provided in this embodiment uses MB15 magnesium alloy parts as magnesium alloy, and prepares the composite coating on the MB15 magnesium alloy parts, including a micro-arc oxidation layer and a gel layer, wherein the content of Ag element in the micro-arc oxidation layer is 0.067%, the content of Zn element is 0.75%, and the content of Ti element in the gel layer is 8.6%.

[0109] The sol-gel process is as follows:

[0110] First, a first solution and a second solution are prepared respectively, wherein the first solution includes ethanol and butyl titanate, the mass ratio of ethanol to butyl titanate is 5:4, and the second solution includes ethanol and diethanolamine, the mass ratio of ethanol to diethanolamine is 5:0.1.

[0111] Microscopic analysis of the prepared magnesium alloy composite coating showed that the thickness of the magnesium alloy composite coating was about 127 μm, the thickness of the micro-arc oxidation layer was about 41 μm, and the thickness of the gel layer was about 86 μm.

[0112] Comparative Example 1:

[0113] Based on Example 1, the following parameters were adjusted in Comparative Example 1.

[0114] This comparative example provides a magnesium alloy coating. The magnesium alloy is MB15 magnesium alloy parts. The coating is prepared on the MB15 magnesium alloy parts. The coating only includes a micro-arc oxidation layer.

[0115] The method for preparing the magnesium alloy coating of this comparative example omits step S4.

[0116] Comparative Example 2:

[0117] Based on Example 1, the following parameters were adjusted in Comparative Example 2.

[0118] This comparative example provides a magnesium alloy coating. The magnesium alloy is MB15 magnesium alloy parts. The coating is prepared on the MB15 magnesium alloy parts. The coating only includes a gel layer.

[0119] In the preparation method of the magnesium alloy coating of this comparative example, step S3 is omitted, and in step S4, the sol-gel is directly sprayed on the magnesium alloy surface of S2.

[0120] Comparative Example 3:

[0121] Based on Example 1, the following parameters were adjusted in Comparative Example 3.

[0122] The magnesium alloy composite coating given in this comparative example uses MB15 magnesium alloy parts as the magnesium alloy. The composite coating is prepared on the MB15 magnesium alloy parts, including a micro-arc oxidation layer and a gel layer. The content of Ag element in the micro-arc oxidation layer is 0.021%, and the content of Zn element is 0.32%.

[0123] The process of micro-arc oxidation treatment is as follows:

[0124] Prepare an electrolyte, the electrolyte comprising: 1 g / L zinc oxide and 0.05 g / L silver nitrate.

[0125] After continuous micro-arc oxidation for 20 minutes, the sample was rinsed with deionized water and dried to obtain a micro-arc oxidation layer containing Ag and Zn elements.

[0126] Comparative Example 4:

[0127] Based on Example 1, the following parameters were adjusted in Comparative Example 4.

[0128] The magnesium alloy composite coating given in this comparative example uses MB15 magnesium alloy parts as magnesium alloy. The composite coating is prepared on the MB15 magnesium alloy parts, including a micro-arc oxidation layer and a gel layer, wherein the content of Ti element in the gel layer is 5.5%.

[0129] The sol-gel process is as follows:

[0130] A first solution and a second solution are respectively prepared, wherein the first solution includes ethanol and butyl titanate, the mass ratio of ethanol to butyl titanate is 5:1, and the second solution includes ethanol and diethanolamine, the mass ratio of ethanol to diethanolamine is 5:0.1.

[0131] Comparative Example 5:

[0132] Based on Example 1, the following parameters were adjusted in Comparative Example 5.

[0133] In the magnesium alloy composite coating of this comparative example, the magnesium alloy is MB15 magnesium alloy parts, and the composite coating is prepared on the MB15 magnesium alloy parts, including an oxide layer and a gel layer.

[0134] The oxidation process adopts a chemical oxidation method, and the content of F element in the oxide layer is 8.2%, the content of O element is 10.5%, the content of Zn element is 0.3%, and Ag is not included.

[0135] The phases of the oxide layer include MgO, MgF2, ZnO, etc.

[0136] Step S3: performing fluoride oxidation treatment on the roughened MB15 magnesium alloy part, and drying the part to obtain an oxide layer containing Mg, Zn, and F elements.

[0137] Performance Test:

[0138] The samples obtained in the above examples and comparative examples were subjected to performance tests, and the specific test conditions and steps are as follows:

[0139] Hemispherical emissivity test: The hemispherical emissivity test performed on the samples obtained from each embodiment and comparative example was performed with reference to GJB 2502.3-2006 “Test Methods for Thermal Control Coatings of Spacecraft Part 3: Emissivity Test”.

[0140] Solar absorption ratio test: The hemispherical emission test on the samples obtained from each embodiment and comparative example was carried out with reference to GJB 2502.2-2006 “Test Methods for Thermal Control Coatings of Spacecraft Part 2: Solar Absorption Ratio Test”.

[0141] Anti-mildew test, antibacterial rate test: The hemispherical emission test on the samples obtained from each embodiment and comparative example was carried out with reference to GJB 150.10 "Military Equipment Laboratory Environmental Test Method Mold Test".

[0142] Neutral salt spray test: The neutral salt spray test is conducted according to the conditions given in GB 2423.17-2008 Environmental testing for electrical and electronic products Part 2: Test method Test Ka: Salt spray, and the neutral salt spray resistance time of the samples obtained in each embodiment and comparative example is determined according to the test standard.

[0143] Table 1 Test results of various embodiments and comparative examples

[0144]

[0145]

[0146] It can be seen from the above table that the hemispherical emissivity, solar absorption ratio, mildew resistance level, antibacterial rate, and neutral salt spray resistance of Examples 1-4 all meet the application requirements. Figure 3 , Figure 4 shown.

[0147] For Comparative Example 1, the magnesium alloy coating only includes the micro-arc oxidation layer. The hemispherical emissivity, solar absorption ratio, and mildew resistance level of the sample in Comparative Example 1 have decreased to a certain extent, the antibacterial rate has decreased by half, and the neutral salt spray resistance performance is obviously insufficient. That is, the lack of the gel layer will greatly reduce the neutral salt spray resistance performance of the magnesium alloy coating. In addition, without the protection of the gel layer, the Ag and Zn elements contained in the micro-arc oxidation layer cannot fully exert the mildew and antibacterial properties.

[0148] The magnesium alloy coating of Comparative Example 2 only includes a gel layer, and the antibacterial rate of the sample of Comparative Example 2 is greatly reduced, and is also lower than that of the sample of Comparative Example 1. This shows that the antibacterial performance of the gel layer containing Ti alone is obviously insufficient. At the same time, the neutral salt spray resistance of the gel layer alone is also significantly reduced compared with the composite coating.

[0149] In Comparative Examples 3 and 4, the Ag and Zn contents of the sample in Comparative Example 3 decreased, the mildew resistance level and antibacterial rate decreased significantly, and the neutral salt spray resistance performance remained unchanged. The Ti content of the sample in Comparative Example 4 decreased, the mildew resistance level and antibacterial rate decreased significantly, and the neutral salt spray resistance performance also decreased. This is mainly because the Ti element plays an obvious role in the formation of the gel layer membrane skeleton, and the decrease in the Ti element content will affect the overall performance of the gel layer. Comparative Example 5 uses fluoride oxidation to form an oxide layer, and a gel layer is attached to the surface of the oxide layer. The mildew resistance level and antibacterial properties of the sample in Comparative Example 5 are obviously insufficient, and the neutral salt spray resistance performance is also lower than that of the micro-arc oxidation layer. On the one hand, the oxide layer formed by fluoride oxidation does not contain Ag elements, and the content of Zn elements is also low. On the other hand, the oxide layer formed by fluoride oxidation has weaker adhesion to the magnesium matrix or the gel layer than the micro-arc oxidation layer.

[0150] The present invention provides a magnesium alloy composite coating and a preparation method thereof, which at least comprises the following steps:

[0151] Beneficial effects:

[0152] (1) The present invention adopts the preparation process of micro-arc oxidation and sol-gel to obtain a composite coating attached to a magnesium alloy. The micro-arc oxidation film layer and the gel layer improve the corrosion resistance of the magnesium alloy substrate. The appropriate amount of Ag and Zn elements added to the micro-arc oxidation layer and the appropriate amount of Ti element added to the gel layer also improve the antibacterial ability of the magnesium alloy substrate, and simultaneously realize the functions of thermal control, corrosion protection and antibacterial on the surface of materials such as magnesium alloys for electronic products and semiconductor devices.

[0153] (2) The present invention constructs a micron-level metal oxide by using a micro-arc oxidation layer and a gel film layer in the magnesium alloy composite coating to achieve a hemispherical emissivity higher than 0.85, which can meet the heat dissipation requirements of electronic products such as cabin chassis and frames.

[0154] (3) In the micro-arc oxidation process of the present invention, sodium silicate and sodium pyrophosphate are used as the main salts of micro-arc oxidation, and are mainly used to be adsorbed on the surface of parts as the main film-forming substances during the micro-arc oxidation process.

[0155] Sodium succinate, potassium hydroxide and ammonia water are used as auxiliary film-forming agents, which mainly play the role of adjusting pH value, stabilizing the micro-arc oxidation solution system and assisting film formation. Zinc oxide and silver nitrate are used as antibacterial additives, which have the effect of inhibiting bacterial growth.

[0156] (4) In the sol-gel process of the present invention, butyl titanate is used as the main salt of the sol-gel and is mainly used as the main film-forming substance to form the film layer skeleton in the sol-gel process.

[0157] Ethanol and diethanolamine, as solvents and auxiliary film-forming agents, mainly play the role of regulating the hydrolysis and cross-linking speed of butyl titanate.

[0158] (5) The magnesium alloy composite coating preparation process provided by the present invention has the advantages of simple process route and convenient operation. The formed thermal control anti-corrosion and antibacterial coating has a wide spectrum of antibacterial effects and good spatial environmental stability.

[0159] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a magnesium alloy composite coating, characterized in that: The magnesium alloy composite coating comprises: a micro-arc oxidation layer and a gel layer, wherein the micro-arc oxidation layer comprises Ag and Zn elements, and the gel layer comprises Ti element; wherein the content of Ag element in the micro-arc oxidation layer is not less than 0.05%, and the content of Zn element is not less than 0.6%; and the content of Ti element in the gel layer is not less than 8%; The method specifically comprises the following steps: S1: Wipe with organic solvent to clean the oil stain on the surface of magnesium alloy; S2: The magnesium alloy of S1 is roughened so that the roughness is not less than 3.2; S3: performing micro-arc oxidation treatment on the magnesium alloy of S2, and drying it to obtain a micro-arc oxidation layer containing Ag and Zn elements; S4: spraying solvent gel on the surface of the micro-arc oxidation layer containing Ag and Zn elements obtained in S3, drying, and attaching a gel layer containing Ti elements on the surface of the micro-arc oxidation layer containing Ag and Zn elements to obtain a magnesium alloy composite coating; Step S3 specifically includes the following steps: S31: preparing an electrolyte, the electrolyte comprising: 8-15 g / L sodium silicate, 10-15 g / L sodium pyrophosphate, 8-15 g / L sodium succinate, 10-15 g / L potassium hydroxide, 10-15 mL / L ammonia water, 2-3 g / L zinc oxide, and 0.1-0.2 g / L silver nitrate; S32: using the magnesium alloy obtained in S2 as an anode, placing it in an electrolytic cell with an electrolyte, applying a DC voltage to the anode and the cathode to generate a micro-arc discharge, wherein the temperature of the electrolyte is 15-35° C., the forward voltage is 460-500 V, the forward duty cycle is 10-20%, the forward frequency is 800-1000 Hz, and the negative voltage is 60-80 V, the negative duty cycle is 5%-10%, and the negative frequency is 500-600 Hz; S33: After the micro-arc oxidation lasts for 30 to 40 minutes, the micro-arc oxidation layer is rinsed with deionized water and dried to obtain a micro-arc oxidation layer containing Ag and Zn elements; Step S4 specifically includes the following steps: S41: preparing a first solution and a second solution respectively, wherein the first solution comprises ethanol and butyl titanate, the mass ratio of ethanol to butyl titanate is 5:(2-4), and the second solution comprises ethanol and diethanolamine, the mass ratio of ethanol to diethanolamine is 5:(0.08-0.13); S42: the first solution and the second solution are mixed to form a mixed solution, and the mixed solution is magnetically stirred for 1 to 3 hours at a stirring temperature of 50 to 60° C. to obtain a sol-gel; S43: spraying the sol-gel onto the surface of the micro-arc oxidation layer containing Ag and Zn elements obtained in S3 with a spray gun, wherein the distance between the spray gun and the surface of the micro-arc oxidation layer containing Ag and Zn elements is 40 to 70 cm during spraying, and the number of spraying is 3 to 5 times; S44: After spraying, drying is performed to obtain a gel layer containing Ti elements attached to the micro-arc oxidation layer containing Ag and Zn elements.

2. The method for preparing a magnesium alloy composite coating according to claim 1, characterized in that: The phases of the micro-arc oxidation layer include Ag2O, ZnO, and MgO, and the phases of the gel layer include TiO2, (TiO) n ,TiO(OH)2.

3. The method for preparing a magnesium alloy composite coating according to claim 1, characterized in that: The thickness of the magnesium alloy composite coating is 100-140 μm, the thickness of the micro-arc oxidation layer is 30-50 μm, and the thickness of the gel layer is 70-90 μm.

4. The method for preparing a magnesium alloy composite coating according to claim 1, characterized in that: Hemispherical emissivity ≥ 0.85, solar absorption ratio ≤ 0.4, absorption-emission ratio ≤ 0.5, mildew resistance level ≤ Level 1, antibacterial rate ≥ 90%, neutral salt spray resistance ≥ 192h.

5. The method for preparing a magnesium alloy composite coating according to claim 1, characterized in that: In step S2, the roughening treatment includes at least one of sandblasting, grinding, alkali washing, acid washing, and activation.

6. The method for preparing a magnesium alloy composite coating according to claim 1, characterized in that: In step S33, the drying temperature is 60-80°C and the drying time is 1-2 hours.

7. The method for preparing a magnesium alloy composite coating according to claim 1, characterized in that: In step S44, the drying is carried out by first drying in the shade and then drying by heating. The drying time is 3 to 5 hours, the drying temperature is 60 to 80° C., and the drying time is 20 to 30 hours.

Citation Information

Patent Citations

  • Preparation of magnesium alloy surface high corrosion resistance differential arc oxidation compound film

    CN101469439A

  • Magnesium or magnesium alloy material used for biological implantation and preparation method thereof

    CN102389588A